1998
DOI: 10.1109/10.661272
|View full text |Cite
|
Sign up to set email alerts
|

A periodogram-based method for the detection of steady-state visually evoked potentials

Abstract: The task of objective perimetry is to scan the visual field and find an answer about the function of the visual system. Flicker-burst stimulation--a physiological sensible combination of transient and steady-state stimulation--is used to generate deterministic sinusoidal responses or visually evoked potentials (VEP's) at the visual cortex, which are derived from the electroencephalogram by a suitable electrode array. In this paper we develop a new method for the detection of VEP's. Based on the periodogram of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 3 publications
1
29
1
Order By: Relevance
“…Our results generally agree that both f1 and f2 responses are identified in response to periodic stimulation with differential amplitude responses that vary with frequency. Our results do not agree with the findings of Liavas et al (1998), who found a distinct separation in the harmonics identified in response to foveal stimulation (f1, f2, f3 and f4) compared to peripheral stimulation (only f2). Overall, it appears that the visual system is sensitive to the frequency components associated with oscillating stimuli.…”
Section: Dorsal Stream Hypothesiscontrasting
confidence: 82%
“…Our results generally agree that both f1 and f2 responses are identified in response to periodic stimulation with differential amplitude responses that vary with frequency. Our results do not agree with the findings of Liavas et al (1998), who found a distinct separation in the harmonics identified in response to foveal stimulation (f1, f2, f3 and f4) compared to peripheral stimulation (only f2). Overall, it appears that the visual system is sensitive to the frequency components associated with oscillating stimuli.…”
Section: Dorsal Stream Hypothesiscontrasting
confidence: 82%
“…• Statistical assessment (''objective response detection'') is relatively easy if performed in the frequency domain (e.g., [1][2][3][4][5]). • In some cases (e.g., flicker electroretinogram), the high stimulation rate is chosen for physiological reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used method to detect SSVEP responses is to apply a Fast Fourier Transform of the EEG signals and to find the corresponding peaks in the ensuing spectra [16]. However, this direct method is sensitive to noise and interference signals when the EEG signals are processed independently.…”
Section: A Steady-state Visual Evoked Potentialsmentioning
confidence: 99%